LIMITATION OF AUTONOMY OF WILL IN THE RIGHT TO DISPOSE OF AN UNWRITTENED MORTGAGE AND TO RETAIN THE PRIORITY ORDER FOR A NEW MORTGAGE - Jeremic, Marina (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
With the entry into force of the law governing the procedure of registration in the real estate cadastre, in addition to the category of the person liable for delivery, a rule was introduced that the procedure of registration is initiated and conducted ex officio. With such a legal solution, the registration of rights is carried out automatically, without any influence of the person in whose favor the right is registered, as well as other interested parties, which restricts the freedom to realized and protect the civil subjective rights of the parties. The registration of ex officio rights with the participation of notaries public as the obligor of the delivery was also reflected in the provisions of the law governing the mortgage, which resulted in the restriction of subjective rights in the registration of the deletion of the mortgage. The paper pays special attention to the limitation of the autonomy of the will of the property owner in realizing the right to dispose of an unwritten mortgage and the right to retain the priority order for a new mortgage. In that sense, it will be pointed out the need to legally regulate the possibility that the procedure of registration of deleting a mortgage is performed at the request of a party.